Valorization of nano additives effects on the physical, mechanical and radiation shielding properties of high strength concrete - Mohamed A. Abouelnour; Islam N. Fathy; Alaa A. Mahmoud; Mansour Alturki; Mohamed M. Abdelaziz; Sahar A. Mostafa; K. A. Mahmoud; Hany A. Dahish; Islam M. Nabil; Mohy S. Fattouh (Scientific Reports)
Abstract This study evaluated the impact of nano silica (NS) and nano metakaolin (NMK) on high-strength concrete (HSC). Portland cement was partially replaced with varying amounts of NS and NMK, both individually and in combination. Portland cement was partially replaced with varying percentages (1, 2, 3, and 4 wt%) of NS and (2, 4 and 6 wt%) of NMK in individual mixes. Four concrete mixtures were formulated using a combination of NS and NMK. The physical properties (slump, consistency, and setting times), mechanical properties (compressive and tensile strengths at 28 days), and microstructural analysis (X-ray diffraction (XRD) and energy-dispersive X-ray (EDX)) were conducted on both the individual and combined mixtures, along with the control mix. Radiation shielding properties of the concrete were conducted. The Monte Carlo simulation code and the Phy-X program were used to examine the efficacy of these combinations in shielding against ionizing radiation, e.g., gamma rays and fast neutrons. The results showed NS and NMK reduced slump in HSC, primarily due to increased water demand and a denser structure. Combined use led to a more significant reduction than individual. Increased NS and NMK content led to higher water demand but shorter setting times. NS improved compressive and tensile strengths, reaching a maximum of 10.5% and 5.6%, respectively, at replacement 3% NS. NMK increased compressive and tensile strengths of 11.7% and 6.3%, respectively at replacement 4% NMK. The combined mixture 1% NS + 4% NMK mixture, demonstrated enhancement in compressive and tensile strengths by 14.2% and 7.7%, respectively, compared to the control mix. XRD and EDX analyses confirmed that NS and NMK enhanced the formation of calcium silicate hydrate and calcium aluminate hydrate through pozzolanic reactions. The linear attenuation of the concrete samples was NMK4 < CM2 < NS3 < C0. The sample containing NMK demonstrated the best value for the linear attenuation coefficient of gamma rays and a rise in FCS, indicating that it is an excellent barrier against both gamma rays and neutrons. These findings demonstrate that NS and NMK significantly enhance HSC strength and radiation shielding, offering safer and more durable concrete for nuclear and medical facilities.